2023
DOI: 10.3390/diagnostics13071252
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Behavior of Left-Ventricular Strain in Fetal Growth Restriction

Abstract: Fetal growth restriction (FGR) is associated with an increased risk of adverse outcomes resulting from adaptive cardiovascular changes in conditions of placental insufficiency, leading to cardiac deformation and dysfunction, which can be evaluated with 2D speckle tracking echocardiography (2D-STE). The aim of the present study was to evaluate whether reduced fetal growth is associated with cardiac left-ventricle (LV) dysfunction, using 2D-STE software widely used in postnatal echocardiography. A prospective lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(91 reference statements)
1
2
0
Order By: Relevance
“…Differences in longitudinal strain in FGR have been previously reported [ 14 , 16 ], even in the absence of Doppler abnormalities [ 8 ], highlighting poorer ventricle contractility in FGR when compared to adequate for gestational age fetuses (AGA) and demonstrating a subclinical cardiac dysfunction in these fetuses, similarly to that described by other studies [ 4 , 19 ]. Previously published studies have also demonstrated the efficacy of different echocardiographic tools [ 4 , 5 , 8 , 20 , 21 ] in assessing cardiac dysfunction associated with FGR.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Differences in longitudinal strain in FGR have been previously reported [ 14 , 16 ], even in the absence of Doppler abnormalities [ 8 ], highlighting poorer ventricle contractility in FGR when compared to adequate for gestational age fetuses (AGA) and demonstrating a subclinical cardiac dysfunction in these fetuses, similarly to that described by other studies [ 4 , 19 ]. Previously published studies have also demonstrated the efficacy of different echocardiographic tools [ 4 , 5 , 8 , 20 , 21 ] in assessing cardiac dysfunction associated with FGR.…”
Section: Discussionsupporting
confidence: 66%
“…Previously published studies have also demonstrated the efficacy of different echocardiographic tools [ 4 , 5 , 8 , 20 , 21 ] in assessing cardiac dysfunction associated with FGR. Due to the technical limitations these tools have, recent studies focused their interest on the evaluation of fetal ventricular strain by 2D-STE [ 11 , 13 , 14 , 22 , 23 ]. In this context, speckle-tracking has emerged as promising solution, offering a semi-automated analysis that reduces intra- and interobserver variability [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation